Analyzing the journey and future trajectories of clean cooking research in India: a bibliometric analysis and case study research - Amardeep Yadav; Vinith Kumar Nair; P. K. Viswanathan; P. Manoj; Raghu Raman (Discover Sustainability)
Abstract The clean cooking challenge in India is deeply intertwined with socioeconomic, cultural, and infrastructural barriers. Despite government initiatives, a significant portion of the population still depends on solid biomass for cooking, leading to severe health, environmental, and social consequences. Energy poverty limits access to affordable clean fuels, especially for low-income households, creating a complex scenario where economic growth alone does not drive a shift toward cleaner cooking options. Our study identifies three primary research themes in clean cooking: accessibility in rural areas, advancements in cookstove technology, and health impacts of indoor air pollution, particularly for vulnerable groups. This research aligns closely with SDG 7 (Affordable & Clean Energy) and contributes to SDGs 3 (Health) and 13 (Climate Action), highlighting the broader benefits of transitioning to cleaner energy sources. However, gaps remain in addressing SDGs 4 (Education), 16 (Institutions), and 17 (Partnerships), pointing to a need for greater policy integration and collaborative efforts. The case studies further illustrate challenges and disruptions caused by COVID-19, including setbacks in clean fuel programs and increased indoor pollution, emphasizing the urgency for supportive policies. India’s clean cooking policies have implications not only for its socioeconomic and environmental health but also for setting a regional benchmark in sustainable energy, positioning the country as a potential leader in clean energy initiatives across Asia. India’s clean cooking policies have implications beyond domestic benefits, potentially serving as a model for sustainable energy practices across Asia and bolstering global progress toward SDG targets.